Muscle Development in Drosophilia - Sink, Helen (Molecular Biology Intelligence Unit, 2006)
The different aspects of muscle development are considered from cellular, molecular and genetic viewpoints, and the text is supported by black/white and color illustrations. The book will appeal to those studying muscle development and muscle biology in any organism.